Identifying Factors Associated with Discontinuation of Infertility Treatment Prior to Achieving Pregnancy: Results of a Nationwide Survey - Barbara Collura MA; Brooke Hayward MS, MBA; Krysten A Modrzejewski PharmD; Gilbert L Mottla MD; Kevin S Richter PhD; Allison B Catherino PhD (Journal of Patient Experience, 2024)
The purpose of this mixed methods, cross-sectional patient survey was to characterize patient experience, to explore the frequency of and reasons for infertility treatment discontinuation and return to infertility treatments. Participants were recruited from United States patient support groups. Participants had received or were receiving ovulation induction (OI) with or without intrauterine insemination (IUI), with or without subsequent in vitro fertilization (IVF), or IVF with no other previous infertility treatment. Live birth was achieved by 62% of participants. Compared with participants treated with OI/IUI only, participants who underwent OI/IUI followed by ≥1 IVF cycle were less likely to consider discontinuing care (64% vs 77%; P  = .014) or to discontinue treatment without achieving a pregnancy (40% vs 58%; P  = .004). The most commonly cited reasons for treatment discontinuation were financial (62%) and psychological burden/treatment fatigue (58%). Expected versus actual time to pregnancy differed greatly. Continued desire for a child (60%) was the most frequently cited reason for continuing or resuming treatment. Expanded access to treatment, counseling and fostering realistic expectations regarding cumulative time to pregnancy may reduce treatment discontinuation.